The application of black garlic (Allium sativum linn) extract cream in preventing the increase level of MMP-1 expression and the decrease of dermal collagen count in the skin of male wistar rats (Rattus norvegicus) exposed to UV-B Rays - Balqis Wasliati; Wimpie Pangkahila; Anak Agung Gede Putra Wiraguna (IJAAM (Indonesian Journal of Anti-Aging Medicine), 2021)
Introduction: UV-B exposure triggers the activation of Protein-1 (AP-1) which disrupts the integrity of the extracellular matrix by inducing MMP-1. Black garlic causes an increase of antioxidant content namely phenolic, flavonoid (quercetin), and DPPH (IC-50). This study aimed to determine the application of black garlic (Allium sativum linn) extract cream in preventing the increased level of MMP-1 expression and the decrease of dermal collagen count in the skin of male Wistar rats exposed to UV-B rays. Methods: This study employed an experimental Post Test Only Control Group Design using 32 male Wistar rats. The rats that were applied with base cream material and exposed to UV-B rays were called the control group. The rats that were applied with 15% black garlic extract cream and exposed to UV-B rays were called the treatment group. The expression of MMP-1 was examined by immunohistochemistry and the dermal collagen count of the skin using Pico-Sirius-Red staining. Results: The mean expression of MMP-1 of the control group was 28.58% and the treatment group was 8.60% (p <0.001). The mean count of collagen in the control group was 57.53% and the treatment group was 83.80% (p <0.001). There was a significant difference in the MMP-1 expression and the count of collagen between the treatment of the control group and the treatment group. Conclusion: Administration of the cream of 15% black garlic extract was proven to prevent an increase MMP-1 expression and decrease dermal collagen count in the skin of male Wistar rats exposed to UV-B rays.